2017
DOI: 10.1111/hepr.12899
|View full text |Cite
|
Sign up to set email alerts
|

Elbasvir/grazoprevir does not worsen renal function in patients with hepatitis C virus infection and pre‐existing renal disease

Abstract: Elbasvir/grazoprevir is a safe and effective treatment option for patients with compromised renal function, irrespective of baseline eGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…17 In a Japanese phase III trial, its SVR rate was 96.5% in chronic hepatitis C patients and 97.1% in cirrhosis patients. 18 Moreover, EBR/GZR could be safely given to patients with comorbid chronic kidney disease, as in the reports by Takeuchi et al and Reddy et al 19,20 The current study, carried out by the Japanese Red Cross Liver Study Group, investigated the outcomes and safety of EBR/GZR treatment, along with its efficacy, in patients with treatment failure with existing DAAs.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…17 In a Japanese phase III trial, its SVR rate was 96.5% in chronic hepatitis C patients and 97.1% in cirrhosis patients. 18 Moreover, EBR/GZR could be safely given to patients with comorbid chronic kidney disease, as in the reports by Takeuchi et al and Reddy et al 19,20 The current study, carried out by the Japanese Red Cross Liver Study Group, investigated the outcomes and safety of EBR/GZR treatment, along with its efficacy, in patients with treatment failure with existing DAAs.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, EBR/GZR could be safely given to patients with comorbid chronic kidney disease, as in the reports by Takeuchi et al . and Reddy et al …”
Section: Introductionmentioning
confidence: 91%
“…Overall, tolerability was favorable given the broad spectrum of Asian participants with significant comorbidities included in this analysis, including those with end‐stage renal disease, HIV co‐infection, inherited blood disorders, and people who inject drugs . Renal function was not evaluated post‐baseline for the majority of participants in this analysis; however, previous studies have confirmed that treatment with EBR/GZR has no impact on renal function …”
Section: Discussionmentioning
confidence: 99%
“…The label explicitly states that no drug adjustment is required for any degree of renal impairment, including hemodialysis. A retrospective, integrated analysis of phase II/III clinical trials for this drug combination found that, among patients with CKD3 (eGFR 30 to <60 mL/min/1.7 m 2 ), 97% of patients achieved SVR without a decline in eGFR either at the end of treatment or 12 weeks after treatment, indicating that this drug combination was both safe and effective …”
Section: Treatmentmentioning
confidence: 99%
“…A retrospective, integrated analysis of phase II/III clinical trials for this drug combination found that, among patients with CKD3 (eGFR 30 to <60 mL/min/1.7 m 2 ), 97% of patients achieved SVR without a decline in eGFR either at the end of treatment or 12 weeks after treatment, indicating that this drug combination was both safe and effective. 52 Based on this clinical evidence, grazoprevir/elbasvir treatment is now a recommended option for patients with CKD or ESRD and HCV genotypes 1 or 4 ( Table 1). Prior to treatment initiation, it is recommended to test for HCV genotype 1 NS5A resistance-associated variants.…”
Section: Treatmentmentioning
confidence: 99%